Retrospective analysis of primary intraosseous malignancies in mandible and maxilla in a population of Taiwanese patients - Chih-Huang Tseng; Wen-Chen Wang; Ching-Yi Chen; Han-Jen Hsu; Yuk-Kwan Chen (Journal of the Formosan Medical Association, 2022)
Background/Purpose: Due to the rarity and diversity of primary intraosseous malignancies in jawbones, we aimed to evaluate the clinicopathological features and discuss the findings of our collected cases with the literatures. Methods: Twenty-nine patients (2000–2020) diagnosed with primary central malignancies of jawbones were selected from the database of Oral Pathology Department in our institution. Clinical features, radiographic appearance, and histopathological diagnosis of the 29 cases were analyzed. Results: Twenty-nine patients aged between 19 and 84 years (average, 57.4 years) with a male to female ratio of 1.2:1 were included. The most frequent site was the mandibular body and ramus, followed by the posterior maxilla and mandibular symphysis. The most common diagnosis was osteogenic sarcoma (n = 13), followed by odontogenic carcinoma (n = 7), hematologic malignancies (n = 5), salivary gland malignancies (n = 2), and neurogenic sarcomas (n = 2). The most frequent symptoms were swelling, pain, paresthesia of lower lip, and mobile tooth. Radiographically, they usually presented as ill-defined osteolytic to osteoblastic lesions depending on the amount of ossification. Wide excision comprising partial maxillectomy and segmental mandibulectomy were the most common therapeutic methods. Conclusion: Despite the rarity of primary central malignancies in jawbones, the clinical features may mimic infectious process or benign lesions. Detailed history-taking, clinical and imaging examination and awareness of the patient's signs and symptoms combining with the histopathological inspection are important for early diagnosis and improved prognosis. The current data contributes a useful basis for clinical investigation regarding intraosseous malignancies occurring in the jawbones.